Módulo web de control de asistencia en los programas de maestría de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López - Solorzano Párraga, Miriam Carolina (2020)
The purpose of this work is to create a web module to control the attendance of students in the master's programs of the Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López". To meet the stated objective, the functional and non-functional requirements were compiled, with respect to the processes related to taking assistance in the master's programs that are in the Postgraduate Directorate, this project was carried out with the agile programming methodology extreme (XP) with its different phases, as part of the methodology, different iterations were carried out based on the user stories and their priority for the development of each of the system modules, the SQL Server Managament Studio software was used for the database design, layout and creation of stored procedures, in the development of the system the Visual Studio development IDE was used, the C # programming language using ASP.NET as a web development environment. The results show that the system carried out made it possible to streamline attendance for students, teachers, reports and the configuration of cohorts. Additionally, the system is linked depending on the ESPAM MFL Academic Management system to avoid duplication of information.